Perancangan Mebel Multifungsi untuk Kantin Gedung W Universitas Kristen Petra Surabaya - Sugiharto, Antonius Christian; Tulistyantoro, Lintu; Kattu, Grace Setiati (Intra, 2019)
The W building canteen of Petra Christian University is one of the facilities that provide food and drinks for students, lecturers, guests, and others. Based on survey results, the problem in the canteen area of W building according to canteen users is that the tables and chairs lack comfort and users need a space to store goods or bags. Therefore, a furniture design is needed to solve problems through Kembel's five design methods consisting of empathize (steps to find problems), define (problem formulation process), ideate (design steps to answer the problem), define (problem formulation process), prototype (producing design outputs), and test (assessment of design results in answering the problems). The design solution is to create a multifunctional table and chair that have a space to store goods or bags. The purpose of the design is to create an interior product that has both use and aest